INTERNALIZATION OF RELIGIOUS VALUES IN EMPLOYEE PERFORMANCE - Diyah Wikan Rahmatika; Muhammad Yusuf Hadiyatullah; Dedeh Yulia (Syari'ah Economics, 2021)
The Muslims have such a strong and fundamental work ethic because it boils down to faith, deals directly with God's power, and is a matter of life and death. A Muslim in every work must be earnest and energetic. In other words, it must be with a high work ethic so that the resulting performance would be more leverage because a Muslim is a more worker (smart-worker). This also applies in an organization or company such as Rabbani which is a company with an activity program that applies Islamic values. This research uses correlational research method, using quantitative approach. Data collection in this study used questionnaires, interviews, and documentation. Data analysis technique used is descriptive statistical analysis, assumption test using normality test, and hypothesis test by using simple linear regression analysis, and t test. Based on the results of this study can be seen that: 1) Islamic work ethic in Rabbani Group Tasikmalaya said good. This is evidenced by the average value of Islamic ethos work variables of 47.77; 2) employee performance in Rabbani Group Tasikmalaya is enough. This is evidenced by the average value of employee performance variables of 30.10; 3) the influence between variables based on the correlation coefficient of 0.373 means that the value belongs to the low level of relationship, that the work ethic of Islami and employee performance have correlation with the low level of relationship. While to see whether or not the influence of this research is done with t test, which shows that t arithmetic of 2.127 with a significance value of 0.042 so that the significance value of 0.042 <0.05 means there is a significant influence between Islamic work ethic variables on employee performance on Rabbani Group Tasikmalaya. Influence is obtained by 13.9% which means employee performance variables influenced by Islamic work ethic variables, while 86.1% influenced by other variables.